QCM sensors functionalized with non-peripheral 5,6,7,8-tetrahydronaph-thalen-2-oxy substituted Phthalocyanines for the detection of metal ions in water samples - Eren, Gozde; Odabas, Zafer; Can, Nursel; Altindal, Ahmet (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Non-peripheral 5,6,7,8-tetrahydronaphthalen-2-oxy substituted metallo (CuPc, CoPc, Mn(OAc)Pc) and metalfree (2HPc) phthalocyanines were designed and synthesized for the detection of Metal Ions (MIs) using a flow-type Quartz Crystal Microbalance (QCM) technique. These novel compounds were synthesized using 3(5,6,7,8-tetrahydronaphthalen-2-oxy)phthalonitrile and appropriate metal salts and characterized by FT-IR, UV-Vis, 1H NMR, 13C NMR, and MALDI-TOF mass spectral data. The effects of metals on spectroscopic properties and aggregation behaviors of the novel phthalocyanines were investigated in different solvents. J-aggregated species were observed in CoPc in the acidic solvents (CH2Cl2 and CHCl3). Acid-induced J-aggregation was confirmed by the destruction of aggregation with the addition of Na2CO3 to the medium. The MI sensing performance of these compounds toward Mg2+, Ni2+, and Co2+ ions, which are selected as representative of hard, soft, and borderline Lewis acids, respectively, was studied experimentally. The results showed that these novel compounds have great potential to detect these metal ions in water within the permissible limits.
Keywords: Phthalocyanine; 5; 6; 7; 8-tetrahydronaphthalen-2-ol; QCM; Metal ion sensing; Adsorption isotherms; PHOTOCHEMICAL PROPERTIES; AGGREGATION; CONDUCTIVITY; PERFORMANCE; REACTIVITY; BEHAVIOR; SYSTEMS; CO(II); MONO; CO2; Spectroscopy